Characteristics of Kraft Pulp and Paper Made from Betong Bamboo (Dendrocalamus Asper) - Ravi, Darshan; Shaiful Rizal Masrol; Mohamad Firdaus Saat; Norsahidah Abdullah (Progress in Engineering Application and Technology, 2025)
The study targets the need to change raw materials to fulfill the increasing requirements in the paper industry by examining the properties of Kraft pulp and paper made from Betong bamboo (Dendrocalamus Asper). This study is to investigate the possibilities of Betong bamboo as a sustainable alternative in light of the constraints of conventional wood supplies. The procedure involves preparing Betong bamboo, pulping it using the Kraft method, and comparing the pulp and paper produced to TAPPI and MS ISO standards. Bulk density, grammage, thickness, bursting strength, tensile strength, and folding durability are among the important properties evaluated. The mechanical and physical characteristics of Betong bamboo pulp are similar to those of commercial and previously researched bamboo products, according to the results. To sum it all up, our study shows that using Betong bamboo as a raw material for high-quality papermaking is possible, encouraging innovation and sustainability in the sector.